A fluorescent hydrazone exchange probe of pyridoxal phosphate for the assessment of vitamin B6 status. Issue 2 (6th December 2019) - Jun, Yong Woong; Hebenbrock, Marian; Kool, Eric T.
Abstract : A new fluorogenic probe based on exchange of hydrazones is described. The probe (Ac-RAB6) is selective for pyridoxal phosphate among the B6 vitamins and other cellular aldehydes, and enables the assessment of abnormal vitamin B6 status in cells. Abstract : Abnormal vitamin B6 status, marked by deficient intracellular concentrations of pyridoxal phosphate (PLP), is classified as a direct biomarker based on its biomedical significance. However, there exist no direct methods for measuring vitamin B6 status in intact cells. Here we describe the development of a fluorogenic probe, RAB6, which shows remarkable selectivity for PLP among the B6 vitamers and other cellular aldehydes.